2011
DOI: 10.1161/circep.111.962928
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fractionated Atrial Electrograms Critical for Maintenance of Atrial Fibrillation

Abstract: Background-Whether ablation of complex fractionated atrial electrograms (CFAE) modifies atrial fibrillation (AF) by eliminating drivers or atrial debulking remains unknown. This randomized study aimed to determine the effect of ablating different CFAE morphologies compared with normal electrograms (ie, debulking normal tissue) on the cycle length of persistent AF (AFCL). Methods and Results-After pulmonary vein isolation left and right atrial CFAE were targeted, until termination of AF or abolition of CFAE bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 35 publications
3
42
0
1
Order By: Relevance
“…51,52 Fractionated electrograms can be fixed and caused by anatomic barriers such as scar or inhomogeneous tissue, or they may be functional, dynamic and related to changes in wavefront propagation throughout the myocardium. It has been further proposed that these fractionated sites are important in sustaining AF, 53 and that targeting fractionated electrograms with ablation can terminate AF and prevent its re-induction or recurrence. 52,[54][55][56][57][58][59][60] The data supporting these conclusions are rather weak overall, with only a few small, randomised clinical trials providing guidance, and different studies have arrived at disparate conclusions regarding the importance, or lack thereof, of fractionated electrograms in the pathogenesis of AF.…”
Section: Limitations Of Targeting Rotors With Ablation For the Treatmmentioning
confidence: 99%
“…51,52 Fractionated electrograms can be fixed and caused by anatomic barriers such as scar or inhomogeneous tissue, or they may be functional, dynamic and related to changes in wavefront propagation throughout the myocardium. It has been further proposed that these fractionated sites are important in sustaining AF, 53 and that targeting fractionated electrograms with ablation can terminate AF and prevent its re-induction or recurrence. 52,[54][55][56][57][58][59][60] The data supporting these conclusions are rather weak overall, with only a few small, randomised clinical trials providing guidance, and different studies have arrived at disparate conclusions regarding the importance, or lack thereof, of fractionated electrograms in the pathogenesis of AF.…”
Section: Limitations Of Targeting Rotors With Ablation For the Treatmmentioning
confidence: 99%
“…20 AFCL has been used by others to monitor response to ablation, with an increase Ն5-6 ms considered significant. [21][22][23] Mean AFCL was determined manually over 30 cycles from bipolar electrograms recorded at the apex of the left and right atrial appendages, where electrograms are high-voltage and hence AFCL is unambiguous, before and after ablation of each CFAE lesion. Baseline AFCL variability was measured over 10 successive segments of 30 cycles in all patients before any ablation.…”
Section: Assessment Of Afclmentioning
confidence: 99%
“…In the CFAE AF Trial they identified that alone CFAE areas were not define the substrate of arrhythmia by themselves, but were only the expression of speed and homogeneity of AF waves, and them had changed to upwards after catheter ablation. [10] Nevertheless it will be the great mistake to underestimate the role of secondary interventional procedures in maintenance of sinus rhythm in late follow-up. In our study we leaned on significance of primary catheter ablation guided by electroanatomical patterns.…”
Section: Resultsmentioning
confidence: 99%